Subject: Compulsory Maths

BODMAS is a common type of rule used in simplification. It means things like add, subtract, multiply, divide, squaring etc. This note has information about BODMAS Rule.

According to BODMAS you must do brackets first, then division, then multiplication, then addition and subtraction. When doing addition and subtraction, it is best to go left to right.

BODMAS is a common type of rule used in simplification. It means things like add, subtract, multiply, divide, squaring etc.

Here,

**BO**refers to Bracket Open

{(3x4)} + {(5x7)}

3 x 4 + 5 x 7**D**denotes Divide

\(\frac{45}{-5}\)

Divide the absolute values

\(\frac{45}{-5}\) = -9

The signs are opposite = -9

Thus, \(\frac{45}{-5}\) = -9**M**refers to Multiply

15 x 4

Multiply the absolute values

15 x 4 =6**A**refers to Addition

-5 + 15

Add the absolute values

-5 + 15 = 10

The sign is positive because we have to put the greater one.**S**denotes Subtract

8 -3

Subtract the absolute values

8 - 3 = 5

The sign is of positive.

- BODMAS stands for Brackets Of Division Multiplication Addition and Subtraction.
- BODMAS is a common type of rule used in simplification. It means things like add, subtract, multiply, divide, squaring etc.

- It includes every relationship which established among the people.
- There can be more than one community in a society. Community smaller than society.
- It is a network of social relationships which cannot see or touched.
- common interests and common objectives are not necessary for society.

Simplify:

-41 -3 (-11)

Solution:

-41 - 3 (-11)

= -41 + 33

= -8

Simplify

-6 × 2 - 12 (-2)

Solution:

-6× 2 - 12 (-2)

= -12 +24

= 12

Simplify:

-24 ÷ (-3) × 5 ÷ 4

Solution:

-24÷ (-3)× 5÷ 4

= 8 × 5 ÷ 4

= 40 ÷ 4

= 10

Simplify :

(-6)^{2} - 4 × 5 (-2)

Solution:

= (-6)^{2} -4 × 5 (-2)

= 36 - 4 × 5 (-2)

=36 -20 (-2)

= 36 + 40

= 76

Simplify

\(\sqrt{20 -4}\) × 8 - 5^{3 } × (2-7)^{2}

Solution:

\(\sqrt{20 - 4}\) × 8 - 5^{3 }× ( 2-7)^{2}

=\(\sqrt{16}\) × 8 - 5^{3 }× (-5)^{2}

= 4 × 8 - 125 × 25

= 32 - 5

= 27

Simplify:

5 - 2 | 7 - 10 |

Solution:

5 -2 | 7 - 10 |

= 5 - 2 | -3 |

= 5 - 2 \(\times\) 3

= 5 - 6

= - 1

Simplify:

- 41 - 3 (-11)

solution:

- 41 -3 (-11)

= - 41 + 33

= -8

Simplify:

25 - 24 ÷ 8 + 3 × 2

Solution:

25 - 24÷ 8 + 3× 2

= 25 -3 + 3× 2

= 25 - 3 + 6

= 31 - 3

= 28

Simplify

- 19 +[ 27 - {14 + ( 5-2) × 4 ÷ 2 }]

Solution:

- 19 +[ 27 - {14 + ( 5-2)× 4÷ 2 }]

= - 19 + [ 27 - { 14 + 3× 2 } ]

= -19 + [ 27 - { 14 + 6} ]

= -19 + [ 27 - 20 ]

= -19 + 7

= -12

Simplify

20 - {8 - (15 +2)}

Solution:

20 - {8 - (15 +2)}

= 20 - { 8 - 17}

= 20 - {8 - 17}

= 20 - {-9}

= 20 + 9

= 29

Simplify:

17 - {19 - 2 (1 + 3)}

Solution:

17 - {19 - 2 (1 + 3)}

= 17 - {19 - 2 \(\times\) 4}

= 17 - {19 - 8}

= 17 - 11

= 6

Simplify:

- 16 + { 8 × ( 2 + 4) }

Solution:

= - 16 + { 8 ×( 2 + 4) }

= - 16 + { 8 × 6 }

= - 16 + 48

= 32

Simplify :

50 ÷ {18 - 4 × 10 ÷ 2}

Solution:

50÷ {18 - 4 × 10 ÷ 2}

= 50 ÷ { 18 - 4 × 5}

= 50 ÷ { 18 -20}

= 50 ÷ { -2}

= - 25

Simplify:

[-20 ÷ {40 - 6 (7 -2 )} ] + 16

Solution:

[-20÷ {40 - 6 (7 -2 )} ] + 16

= [ -20÷ { 40 - 6 \(\times\)5 } ] + 16

= [ - 20÷ { 40 - 30 } ] + 16

= [ - 20÷ 10 ] + 16

= -2 + 16

= 14

Simplify:

5 [152 - {7 - 8 (9-2)}]

Solution:

5 [152 - {7 - 8 (9-2)}]

= 5 [ 152 - {7 - 8 \(\times\) 7}]

= 5 [ 152 - {7 - 56 }]

= 5 [ 152 - { - 49 }]

= 5 [ 152 + 49 ]

= 5\(\times\)201

= 1005

Simplify:

-3 + 7 ( -4)

Solution:

- 3 + 7 ( -4)

= -3 - 28

= - 31

Simplify:

- 5 (- 25) ÷ 25 × (-4)

Solution:

- 5 (- 25) ÷ 25× (-4)

= -5 (-25) ÷ 25× (-4)

= -5 × -1 × -4

= 5 × -4

= -20

Simplify:

11 × 11 ÷ [-11 ÷ {12 - (13 - 12)}]

Solution:

11× 11÷ [-11÷ {12 - (13 - 12) } ]

=11× 11÷ [-11÷ {12 -1}]

= 11× 11÷ [-11÷11 ]

= 11× 11÷ (-1)

= 11× -11

= -121

Simplify:

24 ÷ [18 - 3 {5 + (6-9)}] + 8

Solution:

24÷ [18 - 3 {5 + (6-9)}] + 8

= 24÷ [18 - 3 {5 + (-3)}] + 8

= 24 ÷ [18 - 3 \(\times\) 2] + 8

= 24 ÷ [18 - 6] + 8

= 24 ÷ 12 + 8

= 2 + 8

= 10

Simplify:

[-2 + {11 × (8 + 4) ÷3}] + 21

Solution:

[-2 + {11× (8 + 4)÷3}] + 21

= [ -2 + { 11 × 12 ÷ 3}] + 21

= [ -2 + { 11 × 4 } ] + 21

= [ -2 + 44 ] +21

= 42 + 21

= 63

Simplify:

64 ÷ 8 - 2 [3 + {7 - 3 (3 + 4 - 2)}]

Solution:

64÷ 8 - 2 [3 + {7 - 3 (3 + 4 - 2)}]

= 8 - 2 [ 3 + { 7 - 3 ( 7 -2) }]

= 8 - 2 [ 3 + {7 - 3 \(\times\) 5}]

= 8 - 2 [ 3 + {7 - 15}]

= 8 - 2 [3- 8]

= 8 - 2 \(\times\)- 5

= 8 + 10

= 18

What is the result, when 6 is subtracted from the sum of 5 , 3 and multiplied by 9?

Solution:

According to the question:

{(5 + 3) - 6} \(\times\) 9

= {8 - 6} \(\times\) 9

= 2 \(\times\) 9

= 18

Simplify:

85 - 20 \(\div\) 4 + 10 of 2

Solution:

85 - 20 \(\div\) 4 + 10 of 2

= 85 - 20 \(\div\) 4 + 10 \(\times\) 2

= 85 - 5 + 20

= 80 + 20

= 100

© 2019-20 Kullabs. All Rights Reserved.